Spiritualitas Buddha: Menghadapi Duka Kematian Orang Tua Melalui Penyembuhan Diri - Shelfia Angela; Kabri Kabri; Partono Nyanasuryanadi (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to explore the subjective experiences of grieving and self-healing after parental loss within the framework of Buddhist spirituality. Employing an Interpretative Phenomenological Analysis (IPA) approach, this qualitative study involved five Buddhist adults (>21 years) in Pekanbaru, Indonesia, who had moved beyond the acute phase of grief. The findings reveal that the grieving process is non-linear and deeply influenced by the context of death, the quality of the parent-child relationship, and gender norms. Buddhist teachings—particularly anicca (impermanence) and the practice of pattidāna (merit-transference)—serve as a cognitive framework that facilitates acceptance and transforms grief into meaningful spiritual action. Self-healing mechanisms integrate cognitive reframing, emotional catharsis, and behavioral adaptation. Family support, productive activities, emotional and financial independence, and personal growth were key recovery factors. This study introduces the concept of "Grief as an Ecological-Spiritual Process."